2019
DOI: 10.1186/s41205-019-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of current 3D printed acetabular titanium implants

Abstract: BackgroundThe design freedom allowed by three-dimensional (3D) printing enables the production of acetabular off-the-shelf cups with complex porous structures. The only studies on these designs are limited to clinical outcomes. Our aim was to analyse and compare the designs of different 3D printed cups from multiple manufacturers (Delta TT, Trident II Tritanium and Mpact 3D Metal).MethodsWe analysed the outer surface of the cups using scanning electron microscopy (SEM) and assessed clinically relevant morphome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Two-stage revision remains the gold standard for the treatment of deep periprosthetic hip infection [19]. Performing revision surgery on the hip joint in patients with severe defects in the acetabulum, especially those with pelvic discontinuity, remains a challenge for surgeons [20]. It is worth noting that the purpose of the spacer is not only to treat infection but also to improve the function of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Two-stage revision remains the gold standard for the treatment of deep periprosthetic hip infection [19]. Performing revision surgery on the hip joint in patients with severe defects in the acetabulum, especially those with pelvic discontinuity, remains a challenge for surgeons [20]. It is worth noting that the purpose of the spacer is not only to treat infection but also to improve the function of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators reported that the wall thickness, together with the highly porous surface, contributed to 3D cup stability, allowing peripheral micromotion of the sockets, and at the same time, provided rigidity with the thicker walls[ 11 ]. Dall’Ava et al [ 12 ] evaluated the outer surfaces of three off-the -shelf 3D printed titanium cups (Delta TT, Trident II Tritanium, and Mpact 3D Metal). The three cups have differences as wall thickness, pore size, porosity, and metallic structure.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The three cups have differences as wall thickness, pore size, porosity, and metallic structure. Some molten beads were present, with differences of size and density related to the production technology[ 12 ]. Dall’Ava et al [ 13 ] compared 3D printed cups (Delta TT) with conventional cups (Pinnacle Porocoat, DePuy, United States).…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-printing enables the design and production of complex structures and optimized cup sizes, but its potential risks and clinical impact are still poorly understood [11].…”
Section: Introductionmentioning
confidence: 99%